Dualités et discours du présent dans L’Énigme de Givreuse de Rosny aîné. - Clément Hummel (ReS Futurae, 2016)
Rosny Aîné’s French novel L’Énigme de Givreuse [The Givreuse Enigma], first published in 1917, explores a new theme in speculative literature : the bipartition of a man. On a battlefield in early September 1914, some stretcher-bearers save from wreckages two men absolutely similar and claiming to be Pierre de Givreuse, both ignoring one another’s existence. This astonishing novel from the author of the Xipéhuz (1887) and La Mort de la Terre (The Death of the Earth, 1910) describes the identity crisis of soldiers having come back suddenly from the war to a society which doesn’t accept their infirmity. By creating from nowhere a scientific riddle, Rosny Aîné elaborates on the current advances in science and the social fallout from the conflict, while nothing indicates at the time of publication that it will come to an end. Beyond this plot, L’Énigme de Givreuse allows his author to experiment a new narrative form merging fiction and essay.